Evaluasi Fasilitas Peralatan Pertolongan Kecelakaan Penerbangan dan Pemadam Kebakaran (PKP-PK) di Bandara Haluleo Kendari - Ari Susetyadi (Research and Development Agency of The Ministry of Transportation, 2012)
The airport is an airport pioneering awned by the province of Southeast Sulawesi. The airport was formely named Walter Mongmsidi Airport the condition of that airport still very minimal in term of facilities aid equipment and fire aviation accident (PKP-PK) while the task of airport services every day needs. In the law No. 1 of 2009 on aviation in paragraph 1 has stated that any business entity or unit of an airport operator is obliged to provide airport facilities that meet safety and aviation security and airport services in accordance with established service standards. Flight accident relief unit and fire Department (PKP-PK) is one of the units contained in the organizational structure of airport that are part of the field of ground operations, which have the task to rescue and firefighting aviation accident or fire during take off or landing. Condition of equipment facilities in the PKP-PK Haluleo the airport is currently still requires some facilities, as well as officer are still limited and in part have not been following the training. Bandara Haluoleo adalah bandara perintis yang dimiliki oleh provinsi Sulawesi Tenggara. Bandara ini sebelunmya bemama Bandara Wolter Monginsidi, kondisi bandara tersebut masih sangat minim dalam hal bantuan fasilitas peralatan pertolongan kecelakaan pesawat dan pemadam kebakaran (PKP-PK), sementara tugas pelayanan bandara setiap hari membutuhkan fasilitas yang lengkap Pertolongan Kecelakaan Pesawat dan Pemadam Kebakaran (PKP-PK) merupakan salah satu unit yang terkandung dalam struktur organisasi bandara yang merupakan bagian dari bidang operasi darat, yang memiliki tugas untuk kecelakaan penerbangan, pemadam kebakaran, penyelamatan dan tanggap darurat saat take-off atau landing. Kondisi fasilitas peralatan di PKP-PK Bandara Haluoleo saat ini masih membutuhkan bebexapa fasilitas, serta petugas masih terbatas dan sebagian belum mengikuti pelatihan.